PHP Object Oriented Programming - Safari eBooks ([Place of publication not identified] : Stone River eLearning, 2014)
"This course provides an easy-to-follow guide on one of the most difficult programming concepts, Object Oriented Programming (OOP). The following tutorials we will be discussing classes, methods and properties. These programming concepts will be defined and you will see how they work in a real world situations. You will then move on to more advanced PHP OOP topics. This course is for both experienced and beginning web developers and programmers. We found through student feedback that more instruction was needed on OOP, even if the student had be programming for a number of years. Hence, this course was born. If you're interested in a more in-depth project using Object Oriented Programming, check out our very popular course PHP Object Oriented Programming: Build a Login System."--Resource description page.
Title from resource description page (viewed December 9, 2014)
Presenter, Stone River eLearning.
Keywords: PHP (Computer program language); Scripting languages (Computer science); Programming languages (Electronic computers); Electronic books